2014
DOI: 10.3892/ol.2014.2383
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of Dendrobium candidum Wall ex Lindl. on the formation of lung metastases in BALB/c mice injected with 26-M3.1 colon carcinoma cells

Abstract: Dendrobium candidum Wall ex Lindl. (D. candidum) is a traditional Chinese medicine widely used in Asia. The present study has showed that D. candidum exerted an anti-metastatic effect in mice injected with 26-M3.1 colon carcinoma cells. D. candidum showed the most marked tumor inhibitory rate of 64.5% at a dose of 400 mg/kg body weight (b.w). The mRNA and protein expression of Bax in lung tissue of D. candidum-treated mice was shown to be higher as compared with control mice, whereas the mRNA and protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The orchid D. officinale possesses unique medicinal properties, and has been widely utilized in Asian traditional medicine for the prevention and treatment of various ailments, including obesity, diabetes, hypertension, hyperlipidemia, inflammation, and cancer ( Li L. et al, 2011 ; Li G. et al, 2014 ; Wang Q. et al, 2014 ). A close relative, D. moniliforme , another medicinal orchid, has also recently been reported to exert inhibitory effects on both in vitro RANKL-induced osteoclast differentiation and in vivo lipopolysaccharide-induced bone erosion ( Baek et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The orchid D. officinale possesses unique medicinal properties, and has been widely utilized in Asian traditional medicine for the prevention and treatment of various ailments, including obesity, diabetes, hypertension, hyperlipidemia, inflammation, and cancer ( Li L. et al, 2011 ; Li G. et al, 2014 ; Wang Q. et al, 2014 ). A close relative, D. moniliforme , another medicinal orchid, has also recently been reported to exert inhibitory effects on both in vitro RANKL-induced osteoclast differentiation and in vivo lipopolysaccharide-induced bone erosion ( Baek et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…officinale Kimura et Migo (D. officinale) ( Tiepi Shihu in Chinese) belongs to genus Dendrobium [12] and displays anticancer effects on MCF cells, HCT-116 cancer cells, and HepG2 liver cancer cells in vitro [1315]. Researchers also discovered that D. officinale exhibited preventive effects on the formation of lung metastases and colon carcinogenesis in mice [16, 17]. Our research group has found that D. officinale extraction (DOE) can prevent gastric carcinogenesis in rats through upregulating Bax and downregulating such factors as antiapoptotic B cell lymphoma 2 (Bcl-2), epidermal growth factor (EGF), epidermal growth factor receptor (EGFR), and sphingosine-1-phosphate (S1P) [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Dendrobium candidum has long been used as a traditional Chinese herb drug (Wang et al, 2014). It has a broad range of biological functions, including anticancer activity (Li, Sun, Zhou, et al, 2014), osteoprotection (Wang et al, 2018), and inflammatory regulation effects (Gong et al, 2020). Recent studies also reveal the hepatic therapeutic effect of D. candidum (Li, Sun, Wang, et al, 2014).…”
mentioning
confidence: 99%